SELF-CARE ACTIVITIES AND THEIR RELATIONSHIP TO METABOLIC AND CLINICAL CONTROL OF PEOPLE WITH DIABETES MELLITUS - Anna Claudia Martins Coelhoa (Texto & Contexto Enfermagem, 2015)
Cross-sectional study with the aim to evaluate self-care in people with type 2 diabetes mellitus and verify its relationship with sociodemographic and clinical characteristics. The sample included 218 patients under outpatient follow-up. Self-care activities were evaluated by means of a questionnaire that was previously translated and validated for Brazil. The questionnaire items that reached the highest means were related to drug therapy, whereas those with the lowest means were related to the practice of physical activity. Age correlated inversely with physical activity and foot care, and elapsed time since the disease diagnosis showed a direct correlation with blood glucose monitoring. Data showed that self-care activities related to behavioral changes are the ones that require greater investments to achieve its goals, and age and time since diagnosis should be considered in the planning of nursing care for people with diabetes mellitus.